Vous êtes sur la page 1sur 10

# Page |1

ALL PROOFS
OF
TRIGONOMETRY

XI-Mathematics

## FROM THE DESK OF: FAIZAN AHMED

SUBJECT SPECIALIST
SKYPE NAME: ncrfaizan

## From the Desk of: Faizan Ahmed math.pgseducation.com

Page |2

PROOFS OF TRIGONOMETRY
Fundamental Law:
Consider a unit circle with centre at O(0,0) as shown in figure.
Subject Specialist:
Faizan Ahmed
Merging man and Math

Let P(cos , sin ) and Q(cos , sin ) be any two points in unit circle.
We have distance formula as:
d = ( ) + ( )
Here = ( ) + ( ) ------------------(1)
Now rotate the axes so that the positive direction of X-axis passes through the point P.

Then with respect to this coordinate system, the coordinates of P and Q become (1,0) and (cos( ), sin( ))
respectively.
So, = [ cos( ) 1] + [ (sin( ) 0) ] ------------------(2)
Comparing (1) and (2), we get
( ) + ( ) = [ cos( ) 1] + [ (sin( ) 0) ]
or ( ) + ( ) = [ cos( ) 1] + [ (sin( ) 0) ]
or cos2 2cos .cos + cos2 + sin2 2sin .sin + sin2 = cos2( ) 2cos( ) + 1 + sin2( )
or sin2 + cos2 2cos .cos 2sin .sin + sin2 + cos2 = sin2( )+ cos2( ) + 1 2cos( )
or 1 2cos .cos 2sin .sin + 1 = 1 + 1 2cos( )
or 2cos .cos 2sin .sin = 2cos( )
Dividing by -2, we get
or cos .cos + sin .sin = cos( )

Page |3

## Hence, cos( ) = cos .cos + sin .sin

Law of sin:
Statement:
Law of Sine states that in a triangle measure of the sides are proportional to sine of the angle opposite to theses
\$ &
sides as: = =
!"# !"% !"'
Proof:
We place a ABC in x-, y- coordinate system such that C(0,0) is at the origin and B(a,0) on positive x-axis as shown in the
figure.

\$ ) ,-
As cos(1800 - () = = .,
*)+
,-
Cos1800.cos( - sin1800.sin( = \$
,-
-cos( =
\$
/0 = -b.sin(
*)+ .-
sin(1800 - () = 12* .,
.-
sin1800.cos( cos1800.sin( = \$
.-
sin( =
\$
30 = b.sin(
So the coordinates of A are (b.cos(, b.sin()
Now, If B is taken at the origin

## So, similarly coordinates of A are (c.cos , c.sin )

Hence y-coordinate 30, in both cases is same.
30 = 30
b.sin( = c.sin
\$ &
!"%
= !"' ------------(1)
\$
= ------------(2)
!"% !"#
Comparing (1) and (2), we get
\$ &
!"#
= !"% = !"'

Page |4

## Law of Cosine: c2 =a2 + b2 2abcos4

Proof: We place a ABC in x-, y- coordinate system such that C(0,0) is at the origin and B(a,0) on positive x-axis as
shown in the figure.

\$ ) ,-
We have, cos(1800 - () = = .,
12*
,-
Cos1800.cos( + sin1800.sin( = \$
,-
-cos( = \$
/0 = -b.cos(
*)+ .-
And sin(1800 - () = 12* = .,
.-
Sin1800.cos( - cos1800.sin( = \$
.-
Sin( = \$
30 = b.sin(
So, coordinates of A are (b.cos(, b.sin()
We have distance formula as:
d = ( ) + ( )
Subject Specialist:
Here 35 = c = (6 ( 7) + (6 ( 0) Faizan Ahmed
c= 6 ( 276 ( + 7 + 6 ( Merging man and Math
c= 6 ( + 6 ( 276 ( + 7
c= 6 ( ( + () 276 ( + 7
c = 6 (1) 276 ( + 7
Squaring both sides
c2 = 6 276 ( + 7
And hence, c2 = a2 + b2 2abcos(

9 ;<=>.;<=4
Prove that: = b2
: ;<=@
\$ &
Proof: We have law of sin as:
!"#
=
!"%
=
!"'
\$ \$. !"#
So !"#
= !"% a= !"%
.
& \$ \$. !"'
And !"'
= !"% c= !"%
.
Area of = ac.sin
\$. !"# \$. !"'
= !"%
!"% sin
!"#. !"'
Hence, = b2
!"

## Prove that: = ;(; @)(; B)(; C)

Proof: We have = ac.sin
%
= ac.sin2( )
% %
= ac 2sin .cos [using: sin2x = 2sinxcosx]

## From the Desk of: Faizan Ahmed math.pgseducation.com

Page |5

( E )( E&) ( E\$)
= ac D &

&
&
= ( 7)( 6)( )
&
= ( 7)( 6)( )

Circum-circle: Circle circumscribing is called the circum-circle OR the circle touching the
vertices of is called circum-circle. Its centre is known as circum centre and radius is known as
circum radius denoted by R.

\$ & \$&
Prove that: R = !"#
= !"%
= !"'
and hence show that: R = G
Proof:
Let O be the circum-centre of the circle of ABC. Join O and B and then produce
5I to D. Join C and D. Then 5J = 2R.
If the is acute then m<A = = m<D.
In right BCD
*)+* L,
sin = = =
12* LM N
sin = N
2Rsin = a
Hence, R =
!"#

Now, R =
!"#

R = O R
!" .&Q
P P

R=
(STU)(STV)S(STW)
G D
UV UV

R=
G
UV

\$&
R= G
\$&
R= G
C
In-circle: Circle touching the sides of a is called in-circle. Its centre
is known as in-centre and radius is known as in-radius denoted by r.
Proof: Consider a triangle ABC.
I is the centre of the . Then XY = XZ = XJ = r
Join 3/ , X5, X3.
Here ABC = ABI + BCI + CAI F r E

= cr + ar + br b r I
a
= r (a + b + c)
[\$[,
= rs [using: s = ] r

Hence, r = A B
D
c

## From the Desk of: Faizan Ahmed math.pgseducation.com

Page |6

Prove that: r1 =
; E @
Proof: Consider a ABC in which the e-circle is opposite to vertex
A whose radius is r1 and centre of circle is I1. Join I1A, I1B, I1C.

## Then, ABC = I1CA + I1BA I1BC

= br1 + cr1 ar1
= r1 ( b + c - a ) -----------(1)
[ \$ [ &
As s =
2s = a + b + c
2s 2a = a + b + c 2a
2(s a) = b + c a
(1) = r1 [ 2 ( s a ) ]
= r1 [ 2 ( s a ) ]
= r1 ( s a )
= r1 ( s a )

Hence, r1 =
E Subject Specialist:
Faizan Ahmed
Merging man and Math

Prove that: r2 =
; E B
Proof: Consider a ABC in which the e-circle is opposite to vertex
B whose radius is r2 and centre of circle is I2. Join I2A, I2B, I2C.

## Then, ABC = I2AB + I2BC - I2AC

= cr2 + ar2 br2
= r2 ( c + a - b ) -----------(1)
[ \$ [ &
As s =
2s = a + b + c
2s 2b = a + b + c 2b
2(s b) = a + c - b
(1) = r2 [ 2 ( s b ) ]
= r2 [ 2 ( s b ) ]
= r2 ( s b )
= r2 ( s b )

r2 = E\$

## From the Desk of: Faizan Ahmed math.pgseducation.com

Page |7

Prove that: r3 =
; E C
Proof: Consider a ABC in which the e-circle is opposite to vertex
C whose radius is r3 and centre of circle is I3. Join I3A, I3B, I3C.

## Then, ABC = I3CA + I3BC - I3AB

= br3 + ar3 cr3
= r3 ( b + a - c ) -----------(1)
[ \$ [ &
As s =
2s = a + b + c
2s 2c = a + b + c 2c
2( s c ) = a + b c
(1) = r3 [ 2 ( s c ) ]
= r3 [ 2 ( s c ) ]
= r3 ( s c )
= r3 ( s c )

r3 =
E&

## > ( ;EB )( ;EC)

Prove that: sin = D
: BC
Proof:
As Cosine law says, a2 = b2+ c2 2bc.cos
So, 2bc.cos = b2 + c2 a2
\$P [ & P E P
cos =
\$&
Subtracting from both sides
\$P [ & P E P
1 cos = 1 \$&
# \$&E \$P E & P [ P \
2 sin2 = [using: 1 cosx = 2sin2 ]
\$&
# P E \$ P [ \$& E & P
2 sin2 = \$&
P E ] \$P E \$& [ & P ^
#
2 sin2 =
\$&
P E ( \$ & )P
2#
2 sin = \$&
2# ( [\$ E&)[ E ( \$ E & )]
2 sin = \$&
----------(1)
2# ( [\$ E&)( [ & \$ )
2 sin = \$&
[ \$ [ &
As s =
2s = a + b + c
2s 2c = a + b + c 2c
2(s c) = a + b c
And 2s 2b = a + b + c 2b
2 (s - b) = a + c b
# ( \$ ) ( E& )
(1) 2 sin2 = \$&
# ( \$ ) ( E& )
sin2 = \$&

## From the Desk of: Faizan Ahmed math.pgseducation.com

Page |8

# ( E\$ )( E&)
Hence, sin = D \$&

_ ( ;E@ )( ;EC)
Prove that: sin = D
: BC
Subject Specialist:
Proof: Faizan Ahmed
As Cosine law says, b2 = a2+ c2 2ac cos Merging man and Math
So, 2ac cos = a2 + c2 b2
P [ & P E \$ P
cos = &
Subtracting from both sides
P [ & P E \$P
1 cos = 1
&
2% &E P E & P [ \$P \
2 sin = &
[using: 1 cosx = 2sin2 ]
% \$P E P [ &E & P
2 sin2 = \$&
% \$P E ] P E & [ & P ^
2 sin2 = &
2% \$P E ( & )P
2 sin =
\$&
2% ( \$ [ E& )[\$ E ( E & )]
2 sin = &
----------(1)
2% ( [ \$ E&)( \$ [ & E )
2 sin =
&
[ \$ [ &
As s =
2s = a + b + c
2s 2c = a + b + c 2c
2(s c) = a + b c
And 2s 2a = a + b + c 2a
2 (s - a) = b + c a
% ( & ) ( E )
(1) 2 sin2 =
&
% ( ) ( E& )
sin2 =
&
% ( E )( E&)
Hence, sin = D &

4 ( ;E@ )( ;EB)
Prove that: sin = D
: @B
Proof:
As Cosine law says, c2 = a2+ b2 2ab cos(
So, 2ac cos( = a2 + b2 c2
P [ \$ P E & P
cos( = \$
Subtracting from both sides
P [ \$ P E & P
1 cos( = 1 \$
2' \$E P E \$P [ & P \
2 sin = [using: 1 cosx = 2sin2 ]
\$
' & P E P [ \$E \$P
2 sin2 = \$

## From the Desk of: Faizan Ahmed math.pgseducation.com

Page |9

' & P E ] P E \$ [ \$P ^
2 sin2 = \$
2' & P E ( \$ )P
2 sin =
\$
2' ( &[ E \$ )[& E ( E \$ )]
2 sin = \$
----------(1)
2' ( &[ E\$)( &[\$ E )
2 sin =
\$
[ \$ [ &
As s =
2s = a + b + c
2s 2b = a + b + c 2b
2(s b) = a + c -b
And 2s 2a = a + b + c 2a
2 (s - a) = b + c a
' ( \$ ) ( E )
(1) 2 sin2 =
\$
' ( ) ( E\$ )
sin2 = \$
' ( E )( E\$)
Hence, sin = D \$

> ;( ;E@ )
Prove that: cos = D
: BC
Proof:
As Cosine law says, a2 = b2 + c2 2bc cos >
So, 2bc cos> = b2 + c2 a2
\$P [ & P E P
cos> = \$&
Adding 1 both sides
\$P [ & P E P
1 + cos> = 1 + \$&
> \$[ \$P [ & P E P \
2 cos2 = [using: 1 + cosx = 2cos2 ]
\$&
> (\$ [ &)P E P
2 cos2 = \$&
> (\$ [ & [ )]\$ [ & ^
2 cos2 = \$&
-----------------(1)
[ \$ [ &
As s =
2s = a + b + c
And 2s 2a = a + b + c 2a
2 (s - a) = b + c a
> ( E )
(1) 2 cos2 = \$&
> ( E\$ )
cos2 = \$&
> ( E )
Hence, cos = D
\$&

_ ;( ;EB )
Prove that: cos = D
: @C
Proof:
From the Desk of: Faizan Ahmed math.pgseducation.com
P a g e | 10

## As Cosine law says, b2 = a2 + c2 2ac cos _

So, 2ac cos_ = a2 + c2 b2
P [ & P E \$P
cos_ =
&
Adding 1 both sides
P [ & P E \$P
1 + cos_ = 1 + &
_ &[ P [ & P E \$P \
2 cos2 = [using: 1 + cosx = 2cos2 ]
&
_ ( [ &)P E \$P
2 cos2 = &
2_ ( [ &[ \$)( [ &E \$)
2 cos = &
-----------------(1)
[ \$ [ &
As s =
2s = a + b + c
And 2s 2b = a + b + c 2b Subject Specialist:
Faizan Ahmed
2 (s - b) = b + c b Merging man and Math
_ ( E\$ )
(1) 2 cos2 =
&
_ ( E\$ )
cos2 = &
_ ( E \$)
Hence, cos = D &

4 ;( ;EC )
Prove that: cos = D
: @B
Proof:
As Cosine law says, c2 = a2 + b2 2 76 cos 4
So, 2ab cos4 = a2 + b2 c2
P [ \$P E & P
cos4 = \$
Adding 1 both sides
P [ \$P E & P
1 + cos4 = 1 +
\$
24 \$[ P [ \$P E & P \
2 cos =
\$
[using: 1 + cosx = 2cos2 ]
24 ( [ \$)P E & P
2 cos =
\$
24 ( [ \$ [ &)( [ \$ E &)
2 cos =
\$
-----------------(1)
[ \$ [ &
As s =
2s = a + b + c
And 2s 2c = a + b + c 2c
2 (s - c) = a + b c
4 ( E& )
(1) 2 cos2 = \$
4 ( E& )
cos2 = \$
4 ( E &)
Hence, cos = D
\$